Gas dehydration using glycol solution in absorption and adsorption unit - Mohd Hanafi, Sulaiman (2009)
Gas dehydration is widely used in natural gas treatment plant as a common process, because water and hydrocarbons can form hydrates, which may block valve and pipelines. Water also can cause corrosion in the gas contain acid components. Until today, among the most popular dehydration technology is either absorption or adsorption process. In this research, a novel study on gas dehydration a combination of absorption and adsorption process, where tri-ethylene glycol (TEG) and silica gel are absorbent and adsorbent respectively. A laboratory absorption-adsorption unit is studied in terms of natural gas (methane) flow rate and operating temperature to the percentage of water removal. The experimental work started at room temperature by controlling the valve of methane flow rate at 2.5 m3/hr initially and then allows the gas through the absorption-adsorption unit. Meanwhile, tri-ethylene glycol (TEG) flows at 120 L/hr from a circulation pump. Experiment was repeated with different methane flow rates and different operating temperature in the range of 30oC until 50oC. Experimental results showed that, increasing of methane flow rate causes increasing of water removal while increasing of operating temperature give a result of decreasing of water removal. Thus, in analyzing the gas dehydration efficiency, in an absorption-adsorption unit, parameters such as gas (methane) flow rate and operating temperature are among to be considered for a reliability and economic benefit.-Author-